(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to evaluate the clinical characteristics and microbial causes of lower genital tract infections in pregnant women during the third trimester. Methods: A cross-sectional descriptive study was conducted on 213 third-trimester pregnant women treated for lower genital tract infections at Military Hospital 103, focusing on clinical presentations and etiological agents. Results: The average age of participants was 29.4 ± 0.3 years, with the 24-34 age group accounting for the highest proportion (69.5%). Common clinical signs included grayish-white vaginal discharge (46.9%), vulvar erythema (35.2%), vaginal erythema (65.7%), and cervical ectropion (65.7%). Vaginitis alone was the most common diagnosis (27.2%), followed by 14.1% with combined vulvovaginal and cervical inflammation. The most frequently identified pathogens were Gram-positive cocci (57.7%) and Candida species (24.9%). Conclusion: The study highlights that most third-trimester pregnant women with lower genital tract infections were in the reproductive age group (24-34 years), presenting primarily with grayish-white discharge and vaginal erythema. Gram-positive cocci were the predominant pathogens, followed by fungi, with isolated vaginitis being the most frequent clinical form.